Innovative property for innovative land policy: Four normative principles; Innovatives Bodeneigentum für innovative Bodenpolitik: Vier normative Grundsätze - Benjamin Davy (Raumforschung und Raumordnung / Spatial Research and Planning, 2023)
Innovative land policy does not yield to the pressure of short-term capital exploitation. Rather, innovative land policy establishes a fair balance between the interests of landowners and the public interest. As a keystone of land policy, property -~particularly if open to innovation~- plays a vital role in achieving this balance. This commentary explains four normative principles that help design innovative property. Since the four principles derive from long-standing ideas about property in land, the commentary uses a distinctly conservative approach. This approach, however, is quite innovative in the face of the reductionist view of property as a right that only serves the purposes of its owners. According to the first principle, innovative land policy must pay attention to the nexus between private and common property. Under the second principle, property in land must account for the government's positive duty to provide for adequate land uses for all. The third principle distinguishes between property rights of natural and legal persons: personal property guarantees individual liberty, but corporate property is a social function, not a right at all. The fourth principle reminds of the inseparable bond between property in land and land ethics. – – Innovative Bodenpolitik gibt nicht dem Druck kurzfristiger Kapitalverwertung nach. Stattdessen stellt innovative Bodenpolitik einen gerechten Ausgleich zwischen den Interessen der Bodeneigentümer:innen und dem öffentlichen Interesse her. Als Grundlage aller Bodenpolitik kommt dem Eigentum - vor allem wenn es bereit zur Innovation ist - eine außergewöhnlich wichtige Rolle für die Herstellung dieses Ausgleichs zu. Dieser Kommentar erklärt anhand von vier normativen Grundsätzen die Ausgestaltung von innovativemEigentum. Da die vier Grundsätze aus Ideen über Bodeneigentum gewonnen werden, die bereits vor längerer Zeit entwickelt wurden, verfolgt der Kommentar einen ausgesprochen konservativen Ansatz. Dieser Ansatz beansprucht indes innovativ zu sein, da er den verkürzenden Blick auf Eigentum als subjektives Recht zurückweist, das nur den Eigentümerinnen und Eigentümern dient. Der erste Grundsatz verpflichtet innovative Bodenpolitik zur sorgfältigen Beachtung des Wechselspiels zwischen Privateigentum und Gemeineigentum. Der zweite Grundsatz unterstreicht die staatliche Handlungspflicht zur Gewährleistung angemessener Bodennutzungen für jeden Menschen. Der dritte Grundsatz unterscheidet zwischen dem Eigentum natürlicher und juristischer Personen: Während das Eigentumsrecht von Menschen dem Schutz ihrer Freiheit dient, ist das Eigentum juristischer Personen als soziale Funktion und nicht als Recht anzusehen. Der vierte Grundsatz erinnert an den untrennbaren Zusammenhang zwischen Bodeneigentum und Bodenethik.
Keywords: 710; Individual rights; Land ethics; Land policy; Property; Social function; Bodenpolitik; Eigentum; Soziale Funktion; Subjektive Rechte